Hubungan pijat oksitosin terhadap kelancaran produksi asi ibu post partum - Tuti Meihartati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: The purpose of this study was to determine the relationshipbetween massage breast milk production smoothness of oxytocin onpostpartum mother in BPM Ema Triana, Tanah Bumbu district. This typeof research is analytic survey with cross sectional approach. Number ofsamples of post partum mothers in this study was 36. The sampling techniqueused is Non Probability. Technical analysis using chi-square test with 0.05.Analysis Chi-Square test results obtained significant correlation betweenoxytocin massage (P = 0.001) with the breast milk production smoothnesspost partum. The conclusion from this study is there is a relationshipbetween oxytocin massage on postpartum breast milk production.